akad mudharabah musytarakah dalam asuransi syariah - Bayu Daffa Sumaila; Abdul Mughits (Jurnal Justisia Ekonomika: Magister Hukum Ekonomi Syariah, 2022)
This article is a literature research and the data source used in this research is premier data which is the Al-Quran, Hadith and Positive Law in Indonesia. And secondary data are journals and also books and websites related to insurance and Islamic financial institutions. The analysis used in this research is qualitative-descriptive and the results of this study are the implementation of the mudharabah musytarakah contract is not too familiar among the community so that there are still obstacles in the implementation of insurance services. In addition, Mudharabah Musytaraka is also often used by financial institutions in the banking sector. Mudrabah musytarakah contract is a merger agreement made by the MUI through the Sharia Council Fatwa No. 51/DSN-MUI/III/2006. And also its implementation must be in accordance with Islamic principles.Keywords: Mudharabah Musytarakah, Insurance Services